2021
DOI: 10.1111/jocs.15952
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein and procalcitonin after congenital heart surgery utilizing cardiopulmonary bypass: When should we be worried?

Abstract: Introduction To assess the efficacy of C‐reactive protein (CRP) and procalcitonin (PCT) at identifying infection in children after congenital heart surgery (CHS) with cardiopulmonary bypass (CPB). Materials and Methods Systematic review of the literature was conducted to identify studies with data regarding CRP and/or PCT after CHS with CPB. The primary variables identified to be characterized were CRP and PCT at different timepoints. The main inclusion criteria were children who underwent CHS with CPB. Subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…The cut-off levels were also considerably lower compared to other studies (0.73 mg/L and 1.085 mg/l on the first and third day, respectively). Farias et al reported 12.9 ng/ml cut-off in the infection group compared to 5.6 ng/ml in the non-infection group on the first day post-cardiac surgery; and 15 ng/ml (infection group) compared to 3.6 ng/ml (non-infection group) on the third day post-cardiac surgery ( 28 ). The difference might be attributed to various type of surgeries in our study, which could lead to varying degrees of post-operative inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off levels were also considerably lower compared to other studies (0.73 mg/L and 1.085 mg/l on the first and third day, respectively). Farias et al reported 12.9 ng/ml cut-off in the infection group compared to 5.6 ng/ml in the non-infection group on the first day post-cardiac surgery; and 15 ng/ml (infection group) compared to 3.6 ng/ml (non-infection group) on the third day post-cardiac surgery ( 28 ). The difference might be attributed to various type of surgeries in our study, which could lead to varying degrees of post-operative inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most widely used acute phase marker is CRP, a short pentraxin produced during a systemic inflammatory response (Doni et al, 2017 ). However, due to its kinetics (slow rise and long time to normalization), it is of limited value in postoperative monitoring, and studies have shown that PCT performs better in this setting (Farias et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the pediatric cardiac surgical population have shown the variable utility of CRP and procalcitonin to differentiate between inflammation and severe sepsis in the first week after cardiopulmonary bypass. [29][30][31] We hypothesized that these data would give providers more confidence to stop antibiotics at 24 hours. Although it was underpowered, our exploratory analysis did not reveal absolute values or changes in baseline values that definitively differentiated patients with infection from those without.…”
Section: Discussionmentioning
confidence: 99%